A Comparative Study to Evaluate the Efficacy of Asthisrinkala Lepa and Thriphala Mashi with Pracchanna in the Management of Indraluptha w.s.r. to Alopecia Areata - Sandeep, T S; Rai, Subhash; Kumar, Santhosh (International Research Journal of Ayurveda & Yoga, 2024)
Indralupta is a disease characterized by loss of hair and inhibition of its regrowth. The Alopecia areata is manifested as loss of hair in small round patches. The aggravated vata and pitta cause hair fall and later aggravated kapha and vitiated rakta accounts for its poor regrowth. Pracchanna and lepana are included among various treatment modalities advised for Indralupta. In the present study, Asthisrinkala lepa and Triphala mashi lepa were prepared. A total of 52 patients included were randomly divided into Group A and Group B with 26 patients in each. After doing Pracchanna at the affected area, Group A was treated with application of Asthisrinkala lepa and Group B with Triphala mashi. The results were assessed separately and then comparisons were made between both the treatments. A highly significant (p<0.001) reduction in size of lesion was noted after Pracchanna with Asthisrinkala lepa. Pracchanna with Triphala mashi Lepa also came up with a highly significant reduction in size of lesion after treatment with p value < 0.001. Thus, both procedures were having good and lasting results, but comparing both the groups, Asthisrinkala lepa is more effective clinically than Triphala mashi lepa in Indralupta.